DETERMINANT EFFECT OT CASA AND NPM ON MARKET RATIO OF BANKS LISTED IN IDX - Jennifer; Wirawan Endro Dwi Radianto; Cliff Kohardinata (UNUSA Press, 2022)
Banks are intermediary firms that have an important function in society and countries. Banks’ existence drives the banking industry to increase its financial performance through market ratio growth. This research aims to analyze the influence of CASA and NPM on market ratio for banks listed in the IDX during the period of 2010-2020. The originality of this research is that it focuses on the influence of affordable funds and profitability on market ratio PBV in the banking sector. The research type used is quantitative method with multiple linear regression approach. Sampling techniques used is purposive sampling. The population is 43 banking firms listed in the IDX on December 2020. The sample used is 200 sample data from 21 banks in BUKU II until BUKU IV categories in Indonesia during 11 periods, from 2010-2020. Testing techniques used in this research are descriptive statistics, hypothesis test, and classic assumption test with robust standard error. The research variables consist of a dependent variable (PBV), independent variables (CASA, NPM), control variables (PER, DPR, ROE), and a dummy variable (SOE and private owned). The result of this research is that CASA and NPM have a positive and significant effect on PBV. Hopefully, this research can add consideration for banking management, financial supervisory agencies, investors, and the public about investment making decisions.